2022
DOI: 10.3390/foods11244116
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Products: A Potential Source of Multidrug-Resistant Enterococcus faecalis and Enterococcus faecium Strains

Abstract: This study attempts to present the antimicrobial resistance, virulence and resistance genes of Enterococcus faecalis and Enterococcus faecium isolated from raw goat’s and sheep’s milk and cheese. Strains were identified by PCR. The dominant species was E. faecalis (77.8%) and was most often isolated from raw goat’s milk. The percentage of antimicrobial-resistant E. faecalis isolates was higher than that of E. faecium isolates, the former most frequently resistant to lincomycin (98%), tetracycline (63%) and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The species E. faecalis, E. faecium, E. hirae, E. casseliflavus, and E. durans have been reported to be found in the milk of healthy women [69][70][71]. In our cow milk samples, we found three species-E. faecalis, E. faecium, and E. durans, which is in accordance with other authors' findings [67]. According to some authors, of all reported plant-associated enterococcal species, only E. faecalis, E. faecium, and E. casseliflavus are dominant and best adapted to mammals [69].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The species E. faecalis, E. faecium, E. hirae, E. casseliflavus, and E. durans have been reported to be found in the milk of healthy women [69][70][71]. In our cow milk samples, we found three species-E. faecalis, E. faecium, and E. durans, which is in accordance with other authors' findings [67]. According to some authors, of all reported plant-associated enterococcal species, only E. faecalis, E. faecium, and E. casseliflavus are dominant and best adapted to mammals [69].…”
Section: Discussionsupporting
confidence: 92%
“…An important reservoir for the dissemination of enterococcal populations is the products of the lactation of mammals. For example, the most commonly isolated species from goat and sheep raw milk and their products (cheese) have been reported to be E. faecalis and E. faecium [67]. In our investigation, two similar milk products were analyzed-from cows and humans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Natural resistance to a variety of antibiotics exists in Enterococci, and they are also capable of transferring resistance genes to other microbes via plasmid conjugation mechanisms [33]. Ben Braiek et al (34) mentioned that intrinsic antibiotic resistance of Enterococci includes resistance to cephalosporins, sulphonamides, lincosamides, 𝛽lactams, and aminoglycosides, located in the chromosomes.…”
Section: Resistancementioning
confidence: 99%
“…Biofilms in the food industry also present a food safety threat, as they can act as reservoirs of foodborne spoilage or pathogenic bacteria [113,114], including BA-producing ones [115]. Different phages have been described as potential tools to eliminate biofilms formed by E. faecalis or E. faecium [91,[116][117][118].…”
Section: Food Applications Of Enterococcal Bacteriophagesmentioning
confidence: 99%